2023
DOI: 10.15252/embj.2023113609
|View full text |Cite
|
Sign up to set email alerts
|

Ubx5‐Cdc48 assists the protease Wss1 at DNA‐protein crosslink sites in yeast

Abstract: DNA-protein crosslinks (DPCs) pose a serious threat to genome stability. The yeast proteases Wss1, 26S proteasome, and Ddi1 are safeguards of genome integrity by acting on a plethora of DNAbound proteins in different cellular contexts. The AAA ATPase Cdc48/p97 is known to assist Wss1/SPRTN in clearing DNA-bound complexes; however, its contribution to DPC proteolysis remains unclear. Here, we show that the Cdc48 adaptor Ubx5 is detrimental in yeast mutants defective in DPC processing. Using an inducible site-sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 100 publications
0
8
0
Order By: Relevance
“…Upon 5-aza-dC treatment, DNMT1, DNMT3A and DNMT3B, UHRF1, SUMO2 and SUMO1 were among the most enriched proteins in iPOND-DPC samples (Fig 3d). We also identified factors previously shown to be involved in DPC repair such as the SUMO E3 ligase PIAS4 36,37 , VCP/p97 38,51,52 and most proteasome subunits (Fig 3d, Supplemental Fig 2a; no peptides for RNF4 were detected in any of our samples). Inhibition of SUMOylation abrogated the recruitment of proteins involved in SUMO conjugation, including PIAS1-4, UBE2I and TOPORS as well as VCP/p97 and to some extent the proteasome, but retained DNMT1 enrichment (Fig 3e, Supplemental Fig 2b).…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…Upon 5-aza-dC treatment, DNMT1, DNMT3A and DNMT3B, UHRF1, SUMO2 and SUMO1 were among the most enriched proteins in iPOND-DPC samples (Fig 3d). We also identified factors previously shown to be involved in DPC repair such as the SUMO E3 ligase PIAS4 36,37 , VCP/p97 38,51,52 and most proteasome subunits (Fig 3d, Supplemental Fig 2a; no peptides for RNF4 were detected in any of our samples). Inhibition of SUMOylation abrogated the recruitment of proteins involved in SUMO conjugation, including PIAS1-4, UBE2I and TOPORS as well as VCP/p97 and to some extent the proteasome, but retained DNMT1 enrichment (Fig 3e, Supplemental Fig 2b).…”
Section: Resultsmentioning
confidence: 67%
“…Upon 5aza-dC treatment, DNMT1, DNMT3A and DNMT3B, UHRF1, SUMO2 and SUMO1 were among the most enriched proteins in iPOND-DPC samples (Fig 3d). We also identified factors previously shown to be involved in DPC repair such as the SUMO E3 ligase PIAS4 36,37 , VCP/p97 38,51,52 To uncover proteins that are recruited to DNMT1-DPCs and whose loss causes 5-aza-dC sensitivity, we compared proteins identified to be in proximity of DNMT1-DPCs by iPOND-DPC with the top 2.5% of sensitivity hits in our 5-aza-dC CRISPR screen in DCTD KO cells after plotting the scores of all mutually-occurring hits. This analysis identified the histone methyltransferase SETDB1 and its associated factor ATF7IP, the SUMO ligases PIAS2 and PIAS4, the VCP/p97 adaptor UBXN7 and the interstrand DNA crosslink (ICL) repair protein FANCA (Fig 3g, lower right quadrant).…”
Section: Topors Is Recruited To Dnmt1-dpcs and Promotes Dpc Tolerancementioning
confidence: 97%
“…Finally, Wss1 functions in association with the AAA ATPase/segregase Cdc48 (p97 in mammals), which is targeted to DPCs through adaptors such as Doa1 or Ubx5, which bind Ub‐ or SUMO‐modified proteins. The AAA ATPase/segregase Cdc48 contributes to the processing of the DNA adducts and is able to unfold ubiquitinated proteins for removal or degradation [39,83,85,86].…”
Section: The Role Of Sumo In Dna‐protein Crosslink Repairmentioning
confidence: 99%
“…Besides loss of TOP1 , the loss of UBX5 turned out to be a very strong suppressor in the tdp1Δ wss1Δ background. Indeed, a recent study showed that in the absence of Wss1, the Cdc48‐Ubx5 complex gets trapped on the Flp‐cc FRT locus and prevents access to alternate repair pathways, such as one involving Ddi1 [86]. Other strong suppressors of tdp1Δ wss1Δ were linked to sumoylation, including the Siz2 SUMO ligase and the STUbL subunits Slx5 and Slx8, which, as described above, mediate damage relocation to NPCs, conferring SUMO‐dependent ubiquitination.…”
Section: The Role Of Sumo In Dna‐protein Crosslink Repairmentioning
confidence: 99%
See 1 more Smart Citation